The effects of temperature on endodormancy completion in Japanese pear (Pyrus pyrifolia Nakai) and modeling the relationship - Sugiura, T. (National Inst. of Fruit Tree Science, Tsukuba, Ibaraki (Japan)); Honjo, H (Journal of Agricultural Meteorology, 1997)
The effects of temperature on endodormancy were investigated in flower buds of Japanese pear (Pyrus pyrifolia Nakai cv. ‘kosui’) for the purpose of developing a model estimating endodormancy completion. Potted trees were chilled at constant temperatures (0, 3, 6, 9 and 12°C) from late October for different hours in temperature-controlled dark room. After the chilling treatments, each tree was forced in growth chamber adjusted to 25°C. The endodormancy completion was judged from the percentage of flowering and normal flower after forcing. The chilling for 750h at 0-6°C was necessary to complete endodormancy and 1160h at 9°C was necessary. While at 12°C the endodormancy can not completed. The DVR (Developmental Rate) at each temperature was calculated in the form of reciprocal of the number of chilling hours that were necessary to complete endodormancy (Fig. 3). The model estimating endodormancy completion was obtained from the relationship between the measured DVR and temperature. In order to test the validity of the model, endodormancy completion dates and air temperatures were observed for three years in open field, and the observed hourly temperatures were applied to the model. The model was justified by comparisons between observed and estimated endodormancy completion dates in the field.